E-commerce and legislation in Latin America and Peru - Blas Rivera, Aldrudover (2020)
The E-Commerce evolution, in the world and specially in Latin America, has allowed the increase of exchange between countries; In the same way, countries must regulate this exchange through a set of rules that guarantee that trade is carried out with legal certainty. In this context, Cyberlegislation is the legal instrument that regulates differents aspects of E- commerce. In addition, to promoting national and crossborder commerce of government entities, companies and people with business activities, consumers and citizens, in the dynamic context of the markets